OVA-induced airway hyperresponsiveness alters murine heart rate variability and body temperature - Domnik, Nicolle J.; Seaborn, Geoff; Vincent, Sandra G.; Akl, Selim G.; Redfearn, Damian P.; Fisher, John T. (Frontiers in Physiology, 2012)
Altered autonomic (ANS) tone in chronic respiratory disease is implicated as a factor in cardiovascular co-morbidities, yet no studies address its impact on cardiovascular function in the presence of murine allergic airway (AW) hyperresponsiveness (AHR). Since antigen (Ag)-induced AHR is used to model allergic asthma (in which ANS alterations have been reported), we performed a pilot study to assess measurement feasibility of, as well as the impact of allergic sensitization to ovalbumin (OVA) on, heart rate variability (HRV) in a murine model. Heart rate (HR), body temperature (TB) and time- and frequency-domain HRV analyses, a reflection of ANS control, were obtained in chronically instrumented mice (telemetry) before, during and for 22 h after OVA or saline aerosolization in sensitized (OVA) or Alum adjuvant control exposed animals. OVA mice diverged significantly from Alum mice with respect to change in HR during aerosol challenge (P < 0.001, two-way ANOVA; HR max change Ctrl = +80 ± 10 bpm vs. OVA = +1 ± 23 bpm, mean ± SEM), and displayed elevated HR during the subsequent dark cycle (P = 0.006). Sensitization decreased the TB during aerosol challenge (P < 0.001). Sensitized mice had decreased HRV prior to challenge (SDNN: P = 0.038; Low frequency (LF) power: P = 0.021; Low/high Frequency (HF) power: P = 0.042), and increased HRV during Ag challenge (RMSSD: P = 0.047; pNN6: P = 0.039). Sensitized mice displayed decreased HRV subsequent to OVA challenge, primarily in the dark cycle (RMSSD: P = 0.018; pNN6: P < 0.001; LF: P < 0.001; HF: P = 0.040; LF/HF: P < 0.001). We conclude that implanted telemetry technology is an effective method to assess the ANS impact of allergic sensitization. Preliminary results show mild sensitization is associated with reduced HRV and a suppression of the acute TB response to OVA challenge. This approach to assess altered ANS control in the acute OVA model may also be beneficial in chronic AHR models.